Implementation of the Internet of Things for Monitoring and Protecting Hydrogen Production in Dry Cell HHO Generators - Robby Setiadi; Taqwa, Ahmad; Bow, Yohandri (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
In the last few decades, researchers have been conducting various studies in search of alternative energy sources to reduce dependence on fossil fuels and anticipate future energy scarcity. One such alternative energy is hydrogen, which can be obtained through various methods, including electrolysis of water. Hydrogen possesses the characteristics of being flammable, odorless, colorless, and tasteless, necessitating the development of a rigorous monitoring and protection system to mitigate potential hazards. In this study, a monitoring and protection system was designed for the operation of an electrolyzer using a Dry Cell type HHO Generator. The system employs the concept of the Internet of Things, where data is connected through the internet network. The data received includes hydrogen concentration readings, electrolyzer operation automation, electrolyzer operating status, and hydrogen gas leak detection in the system. The research results obtained showed that the higher the concentration of electrolyte and the voltage supplied to the electrolysis process, the faster the production of hydrogen gas is accelerated, accompanied by an increase in temperature. If a leakage occurs in a system, the occurrence of the fire triangle will be faster when the concentration of electrolyte and the voltage supplied are greater.